IMPACT OF COAL-ROCK DUST AND SODIUM FLUORIDE ON THE SPECIFICITY OF MORPHOLOGICAL CHANGES IN INTERNAL ORGANS IN EXPERIMENTAL ANIMALS - Бугаева, Мария Сергеевна; Бондарев, Олег Иванович; Уланова, Евгения Викторовна (Medicine in Kuzbass, 2024)
The aim of the research was an experimental study of the specificity of morphological change development in internal organs with long-term exposure of the body to various production factors: coal-rock dust and sodium fluoride. Materials and methods. The study was conducted on two experimental models: anthracosilicosis and fluoride intoxication. After 1, 3, 6, 9, 12 weeks of exposure to harmful factors, in experimental animals, the lungs, bronchi, heart, liver and kidneys were sampled for subsequent histological processing. Results. The exposure of the body to coal-rock dust and sodium fluoride leads to the development of adaptive reactions in the internal organs of animals in the 1st-3rd weeks of the experiment, which is a universal mechanism in the early stages. Their further intake causes the formation of organ-specific manifestations depending on the acting factor. Inhalation of coal-rock dust is accompanied by an early breakdown of compensatory mechanisms of the respiratory organs and heart muscle and the formation of pneumosclerosis, atrophy of the bronchial mucosa, and degenerative changes in cardiomyocytes from the 6th week of the experiment. Cardiosclerosis develops by the 12th week. In the liver and kidneys, dystrophic changes in parenchymatous cells are restrained by reparative processes and develop by the 9th week of the experiment. Accumulation of sodium fluoride leads to the early formation of pronounced protein dystrophy of hepatocytes and nephrocytes with the formation of necrotic foci by the 6th-9th weeks of the experiment. Disturbances in the bronchopulmonary system before the 9th week of exposure are of the nature of immune inflammation with subsequent development of degenerative changes in the air-conducting structures. Moderate dystrophy of the parenchymatous component is characteristic of the heart muscle throughout the experiment. Regardless of the influencing production factor, changes in the vessels of the organs under study are characterized by hypertrophy of smooth muscle cells of the media, endotheliosis, hyalinosis and fibrosis of the perivascular zones. Conclusion. Identification of the stages of morphological changes has practical significance for elaboration of recommendations for determining the timing and methods of prevention and correction of disorders caused by exposure to coal-rock dust and sodium fluoride.